COGNITIVE STATUS OF PATIENTS WITH CHRONIC OBSTRUCTIVE LUNG DISEASE ASSOCIATED WITH ARTERIAL HYPERTENSION AND PREDICTORS OF ITS PERFORMANCE - N. B. Poletaeva; O. V. Teplyakova (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2020)
Background. The cognitive status in individuals with chronic obstructive pulmonary disease (COPD) associated with arterial hypertension (AH) has not been adequately studied. The aim of the work was to study the cognitive status of patients with COPD associated with arterial hypertension and establish predictors of its deterioration. Materials and methods. 30 patients with COPD were examined, 30 patients with COPD associated with hypertension (COPD + AH), 30 healthy males. Researchers evaluated the function of external respiration, determined the gas composition of the blood, questionnaired using forms for Beck depression, Spielberg-Hanin anxiety, and two-time testing using the Montreal cognitive function assessment scale (MoCA). Results. Patients with COPD and COPD + AH had low MoCA scores compared to controls, but were comparable. Repeated testing with a difference of 12 months showed the presence of negative dynamics in both nosological groups and revealed correlations between the total score on the MoCA scale and the partial pressure of oxygen and carbon dioxide in the blood, levels of reactive anxiety, and depression. A reliably significant predictor of deterioration was the presence of exacerbations of COPD. Conclusions. In patients with COPD associated with hypertension, a decrease in cognitive function was detected; MoCA scores are predicted by exacerbations over the past year.